Currency in curculation - Zoran Stavreski (National Bank of the Republic of Macedonia, 1998)
Currency in circulation, together with demand deposits, is a component of narrow money which movements are of special interest for policy makers. There are several relevant indicators showing the relative significance of the currency in circulation in particular economy, among which the most important ones are: 1/ share of currency in circulation in money supply; and 2/ ratio of currency in circulation in nominal gross domestic product. Dynamic analyses of these indicators in the Republic of Macedonia shows high degree of cash utilization in performing everyday nominal transactions. The cross country analysis confirms significant role of currency in circulation in the Republic of Macedonia, not only compared to developed countries, but also in terms of countries in transition with similar macroeconomic performances. In order to eliminate factors that determine high degree of cash transactions, several activities have to be operationalized: 1. Launch of more organized and more active modern non-cash payment instruments is essential. This could be done trough a comprehensive project for introduction of a unique payment card, either on the level of whole economy, or at least with participation of several largest commercial banks in the country. The card should be used for both, domestic and international payments. This project can follow the already existing projects in three largest banks, by converging separate projects into one, which will include participation of some small commercial banks. Besides, banks should install more ATM machines (cash points) and should broaden the spectrum of international credit cards and checks. The quality of bank services should also improve, stimulating some household groups to work with checking accounts, etc.; 2. The existing regulation on use of cash should be revised. The most important in this context is to put stricter restrictions on the use of cash by legal entities for making payments. Also, a necessary control should be strengthened and appropriate policy for violation of the regulation should be prescribed; and 3. A reduction of cash payments of salaries and pensions is necessary, as well as a reduction of cash payments for purchased agricultural products. Simultaneously, the orientation to more active use of banks' services and payment trough checking accounts should be stimulated.
Keywords: 330